Bagasse Sebagai Salah Satu Alternatif Campuran Media Tanam Pada Lahan Pekarangan Menuju Kemandirian Pangan Keluarga di Kabupaten Batanghari - Sri Harimurti; Rusnani Rusnani (Jurnal Abdimas ADPI Sains dan Teknologi, 2023)
Teratai is one of the villages located in Muara Bulian District, Batang Hari Regency and is in the middle of the city, with diverse residents' livelihoods. Almost all housewives and young women have a hobby of farming around the plot of the house. The resulting plants can be used as a support in meeting the needs of daily life, so as to realize food independence in the family. One alternative is a mixture of planting media is sugarcane bagasse. Sugarcane bagasse contains 52.67% water, 55.89% C-organic, N-total 0.25%, 0.16% P2O5, and 0.38% K2O. The method of activity is in the form of counseling with the aim of introducing bagasse / bagasse which can be used as an alternative mixture of planting media in the plots and the contents contained therein. The results of the activity do not yet know that bagasse / bagasse can be an alternative mixture of media and only know if bagasse contains sugar, and is very good as a compost mixture.